Risk factors and clinical manifestations of cerebral venous thrombosis in patients admitted to Zahedan city hospitals during 2011-2017 - Amirifard, Hamed; Khosravi, Alireza; Akbarian, Hoseinali (Asian Journal of Medical Sciences, 2018)
Background: In Cerebral venous thrombosis (CVT), blood clots are create in the veins and, blood clots may form in the veins or sinuses. In 78% of cases this problem occurred in people lower than 50 years and in women more than men. The annual prevalence of CVT in Iran was 12.3 per one million which was 2.5 times more than world prevalence. Aims and Objective: The aim of this study was to investigate the Risk factors and clinical manifestations of cerebral venous thrombosis in patients admitted to Zahedan city hospitals. Methods and Materials: This retrospective descriptive study was done on 50 patients with CVT which hospitalized in the Zahedan city hospital. Necessary information such as clinical symptoms, risk factors and demographic data extracted from patients file and analyzed by statistical methods in SPSS.16. Results: In this study, 68% of patients were female and 32% were male. The most prevalent season was summer age group 34-43 years constituting about 28 % of the cases. The prevalent season was summer with 38 % cases and headache was the most prevalent symptom (66%). The most prevalent risk factor was infection comprising 30 % of the total patients. Conclusion: Results showed higher prevalence of CVT in women than in men which could be due to the positive relation between prevalence of this disease and risk factors such as oral contraceptive pill (OCP), pregnancy and post-partum period. Also, in this study the most prevalent symptom was headache and the most prevalent season was summer, which could be due to dehydration of patients. The validity of the current study could be further substantiated with study in the similar pattern with more sample size. Asian Journal of Medical Sciences Vol.9(2) 2018 6-9